Derivatives theory and practice - Cuthbertson, Keith; Nitzsche, Dirk; O'Sullivan, Niall Michael 1971- (Wiley, 2020)
"The aim of this book is to present a clear exposition of key results on pricing, hedging and speculation using derivative securities. The emphasis is on drawing out the practical uses of derivatives. The reader needs only to have undertaken an introductory course in finance, together with some basic statistics and simple algebra, including calculus. The mathematics and statistics have been kept to a minimum, with the emphasis on intuitive explanations and practical applications. For those requiring some revision of basic finance concepts, these can be found in a companion text, Investments, 2nd edition (K. Cuthbertson and D. Nitzsche, John Wiley)"--
Includes bibliographical references and indexes. - Description based on online resource; title from digital title page (viewed on January 06, 2020)
Keywords: Derivative securities; Instruments dérivés (Finances); BUSINESS & ECONOMICS / Finance / Financial Engineering